Analysis and Design of SiC Three-Phase Four-Wire Five-Level E-Type STATCOM Inverter - Zoran Miletic; Petar J. Grbovic; Thierry A. Meynard (IEEE Access, 2024)
In power quality applications, the long-term reliability, low maintenance cost, and low volume and weight of a STATCOM converter are of the paramount importance. The use of the series multi-level power converter topology can significantly improve both volumetric and gravimetric density as well as power conversion efficiency of the STATCOM converter. This paper presents a solution that utilizes the Novel 5 Level E Type topology for the 3-phase, 4-wire STATCOM power quality applications. A comprehensive theoretical analysis and step-by-step design process are presented and discussed in the paper. A proof of the concept prototype (12kVA $3× 400.230$ V) has been designed, manufactured, and intensively tested and experimentally verified. The experimental results are discussed in detail and compared with state-of-the-art solutions from both academic and industrial sectors. The achieved improvements in volumetric and gravimetric density, along with ultra-high power conversion efficiency and reduced cooling effort, justifies significant benefits of the proposed topology and approach.